Optimal timing for bilateral total knee arthroplasty: comparing simultaneous and staged procedures at various intervals: a systematic review and network meta-analysis - Cheng-Yang Chang; Kun-Han Lee; Jui-Chien Wang; Shang-Wen Tsai; Cheng-Fong Chen; Po-Kuei Wu; Wei-Ming Chen (EFORT Open Reviews)
Purpose: A staged bilateral total knee arthroplasty (BTKA) procedure is considered when a patient is not deemed suitable for simultaneous BTKA due to concerns about the risk of mortality and complications. However, no network meta-analysis has been conducted to compare simultaneous vs staged BTKA procedures with different intervals in terms of postoperative mortality and overall complication rates. Methods: Four databases – Medline, Embase, Cochrane Library and Web of Science – were searched from inception to December 19, 2023, for studies comparing patients who underwent staged BTKA with different intervals and simultaneous BTKA. The primary outcome domains were 1-year mortality and 90-day overall complications. Secondary outcomes included neurological, cardiovascular, pulmonary, infectious and venous thromboembolic complications within 90 days. Results: Fifteen observational studies were included. Staged BTKA with intervals between 6 weeks and 3 months (odds ratio (OR): 0.69, 95% CI: 0.53–0.91), between 3 and 6 months (OR: 0.67, 95% CI: 0.53–0.84) and longer than 6 months (OR: 0.67, 95% CI: 0.55–0.83) exhibited a lower mortality risk compared to simultaneous BTKA. Staged BTKA with an interval shorter than 6 weeks and longer than 6 months exhibited a higher risk of pulmonary (OR: 1.24, 95% CI: 1.03–1.49; OR: 1.64, 95% CI: 1.10–2.44) and infectious complications (OR: 1.50, 95% CI: 1.15–1.96; OR: 1.52, 95% CI: 1.14–2.02) compared to simultaneous BTKA. An interval between 3 and 6 months ranked best in outcomes of 1-year mortality (P score = 0.7849) and 90-day complications (P score = 0.7077). Conclusions: Staged BKTA with an interval of more than 6 weeks but less than 6 months is associated with a lower risk of postoperative mortality and complications. However, these results should be interpreted with caution due to potential biases inherent in the inclusion of nonrandomized studies. Level of Evidence: II